The Importance of Cl− Exclusion and Vacuolar Cl− Sequestration: Revisiting the Role of Cl− Transport in Plant Salt Tolerance - Wu, Honghong; Li, Zhaohu (Frontiers in Plant Science, 2019)
Salinity is a global issue that threatens agricultural production systems across the globe. While the major focus of researchers working in the field of plant salinity stress tolerance have always been on sodium and potassium, the transport patterns and physiological roles of Cl− in plant salt stress response are studied much less. In recent years, the role of Cl− in plant salinity stress tolerance has been revisited and received more attention. This review attempts to address the above knowledge gap of chloride in plant salinity stress tolerance. In this review, besides Cl− transport, the role of Cl− extrusion and vacuolar Cl− sequestration in plant salinity stress tolerance were discussed. Furthermore, the identity of channels and transporters involved in Cl− transport in salt stressed plants was also discussed.